2016
DOI: 10.1016/j.ijgo.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of hysteroscopy or ultrasonography versus no guidance during D&C after uterine artery chemoembolization for cesarean scar pregnancy

Abstract: Hysteroscopy or ultrasonography monitoring of D&C after UACE for CSP treatment can decrease the complication rate. ClinicalTrials.gov: NCT02357095.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Several factors are associated with the formation of a PCSP mass. Firstly, a prior study confirmed that a previous cesarean scar defect is a common presentation among women with CSP and trophoblastic tissue is located within the defect, making it inaccessible for surgical evacuation . Thus, the proportion of women who underwent surgical evacuation of CSP diagnosed with retained product of contraception on postprocedure ultrasound examination was higher when compared to women who underwent surgical evacuation of failed intrauterine pregnancies .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Several factors are associated with the formation of a PCSP mass. Firstly, a prior study confirmed that a previous cesarean scar defect is a common presentation among women with CSP and trophoblastic tissue is located within the defect, making it inaccessible for surgical evacuation . Thus, the proportion of women who underwent surgical evacuation of CSP diagnosed with retained product of contraception on postprocedure ultrasound examination was higher when compared to women who underwent surgical evacuation of failed intrauterine pregnancies .…”
Section: Discussionmentioning
confidence: 95%
“…Zhang et al reported that eight patients with PCSP were treated successfully by laparoscopic scar pregnancy resection and scar‐defect repair, while two patients were treated by hysteroscopy . In Li et al .’s study, six patients with PCSP were treated by repeat surgical evacuation with hysteroscopy guidance . In their study, Wu et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, the treatment objective for a CSP is to terminate the pregnancy, reduce bleeding and reserve the patient's fertility. Transvaginal surgical evacuation undersound or hysteroscopy guidance has been widely adopted in China 5,6 . This method not only has minimal invasion and rapid recovery, but also can preserve fertility.…”
Section: Introductionmentioning
confidence: 99%